Modeling and Estimation of Nickel Laterite Resources Using Geocomputing Methods at North Konawa, Southeast Sulawesi - Rohaya Langkoke (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Administratively, the research area is located in the Waturambaha area, North Konawe, Southeast Sulawesi province. The method used in determining the distribution and estimation of Ni laterite measurable resources is one of the geocomputational methods, Inverse Distance Wieght (IDW). From the interpolation of 82 drill points, it was concluded that the distribution of Ni levels is quite high (COG ≥ 1.2%) discriminated dominantly in the central to northern part and some points in the northwest of the study area, while low-grade Ni (<1.2%) is distributed in the northeastern to southeastern part of the study area.   Based on distributed ore modeling in the central to northern parts of the study area on limonite layers with a thickness of 2 – 4 m while in saprolite layers the thickness ranges from 6 – 12 m.  Waste in the limonite layer with a thickness of 5-10 m while in saprolite 4-7 m.   Modeling the distribution of Ni by the IDW method in the study area obtained a measured resource volume of Ni of 1,196,450 m³ which was then multiplied by the density of each layer (limonite and saprolite) and obtained a tonnage of ni measured resources of 1,854,500 M/T with 1.39% ni average.